Glaciers of the Koryak Highlands: assessment of the state using satellite images and field studies - Ananicheva, Maria D.; Aleinikov, Alexander A. (Bulletin of Geography. Physical Geography Series, 2022)
The Koryak Highlands are a poorly explored area in terms of glaciation and its connection to climate. The purpose of this work is, using Sentinel-2 images (2019), to assess the state of glaciers at present against the background of climatic trends. Spatial patterns of trends of mean summer and annual temperatures, total precipitation and precipitation for the cold period from 1966 to 2019 were compiled: the temperature trends increase towards the Kamchatka Peninsula, and the mean summer temperature trends increase from 2 to 3°C. Precipitation trends increase from the continent to the coastal zone, with cold season trends changing from 0 to minus 50 mm. As a result, 212 glaciers and 279 rock glaciers were discovered in the Highlands, whereas 112 objects that had previously been recognised were not identified: either there is no glacier, or its area is less than 0.001 km2. The reduction in glacier areas compared to the USSR Glacier Inventory (1960s) varies widely by river basin, from 35 to 74%. The mean present glacier area varies from basin to basin from 0.4 to 0.11 km2. The glaciers are mainly corrie type of the N, NE and NW aspects. The change of average glacier firn line is from several tens of metres to 400–500 m.